PENGARUH PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) DAN UMUR PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2016-2020 - Rina Marya Ulfah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine whether there is an influence between Islamic Social Reporting and company age on the profitability of companies listed on the Jakarta Islamic Index 2016-2020. The population in this study were 30 companies and in this study used a purposive sampling technique so that the final sample in this study was 14 companies multiplied by 5 periods to 70 samples. This study uses data analysis consisting of descriptive analysis, classical assumption test and hypothesis testing assisted by the SPSS Statistic 21 application. The results show that partially Islamic Social Reporting has no effect on profitability while company age has an effect on profitability. This study also shows that simultaneously Islamic Social Reporting and company age have an effect on profitability.